Emotional stress and psychosocial resilience in urban tourism: A configurational analysis of three Southern European cities - Saucedo-Calzada, R.; Dias, Á.; Almeida-García, F.; Cortés-Macías, R. (International Journal of Tourism Cities, 2026)
Urban tourism has long been associated with economic development, yet it increasingly gives rise to emotional stress and social disruption in densely visited cities. While governance strategies – such as regulation and planning – have received substantial academic attention, less is known about the psychosocial mechanisms through which local communities respond to tourism-related pressures. Addressing this gap, the present study explores how social capital, psychological resilience, and perceived control influence residents’ emotional adaptation in three Spanish cities facing sustained tourism growth: Málaga, Granada, and Seville. Drawing on a dual-method approach – Partial Least Squares Structural Equation Modeling (PLS-SEM) and Fuzzy-Set Qualitative Comparative Analysis (fsQCA) – the study analyses responses from 807 residents. The results indicate that social capital has a nonlinear (inverted U-shaped) effect on resilience, which significantly reduces emotional stress. Perceived control also plays a mediating role, reinforcing residents’ capacity to manage tourism-induced pressures. The fsQCA analysis reveals distinct city-level configurations, suggesting that no single factor is universally sufficient, but rather that different combinations of local resources support residents’ emotional well-being. By shifting the analytical lens from institutional responses to community-level dynamics, this study contributes to the growing literature on the social impacts of tourism. It highlights the importance of integrating emotional and psychosocial dimensions into tourism planning, particularly in urban settings where resident well-being is increasingly at risk.